A new microendemic species of Tropidurus (Squamata: Tropiduridae) from southern Brazil and revalidation of Tropidurus catalanensis Gudynas & Skuk, 1983 - Kunz, Tobias Saraiva; Borges-Martins, Márcio (Zootaxa, 2013)
The South American and cis-andean lizard genus Tropidurus has a complex taxonomic history. Most species were recently described and previous revisions included few specimens from the southern part of the continent. Tropidurus torquatus has the broadest geographic distribution in the genus and several morphological and ecological differences were described within its distribution. We analyzed the geographic variation in external morphological characters of Tropidurus torquatus, including large number of samples from southern Brazil. Tropidurus catalanensis is revalidated and Tropidurus imbituba sp. nov., with a restrict distribution in the southern coast of Brazil, is described. The new species is distinguished from Tropidurus catalanensis by the number of dorsal scales. It can be distinguished from T. catalanensis and T. torquatus by a distinct orange ventral coloration in adults, which can reach the lateral portion of the body in adult males. Our analysis also suggests that at least two other undescribed species could be recognized under the name Tropidurus torquatus in southeastern and central Brazil.